Injury In Preschool-Age Children: A Population-Based Study - Achmad Surjono; Soenarto Sastrowijoto; Siswanto Agus Wilopo; Harun Rusito (Paediatrica Indonesiana, 1995)
A study on the type and frequency of injuries in preschool-age children was conducted in a sample of households representing population of Purworejo district. A two stages cluster (wilcah) method was used to select 4.354 preschool-age children living in 12,721 households in the district. The mother or other child caretakers provided responses about injuries occurring during the 3 months period to interview. Injuries among these preschool-age children included trauma by cutting or sharp object (6.5%), falls (5.7%), bums (0.6%), bites (0.4%), traffic accident (0.4%), unconsciousness (0.2%) and poisoning (0 .1 %). The typical injury in under the 12 months olds was falls. Children aged 12 to 23 month accounted for 18% of the injury episodes which were typical fall and trauma. Children aged 24 to 59 months accounted for 76.6% of injury episodes which were typically trauma, falls, bums, bites and traffic accident. No statistical differences in the frequency and type on injuries were observed between urban and rural areas. The relative frequency in age-grouped and type of injuries from this population-based study can be used in planning injury prevention especially for family health education program.